2012
DOI: 10.1021/jo300713h
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalyzed C–H Functionalization of O-Arylcarbamates: Selective ortho-Bromination Using NBS

Abstract: A series of cyclometalated palladium complexes derived from O-phenylcarbamates has been synthesized by the reaction of the respective carbamates with Pd(OAc)(2) in the presence of acids, CF(3)CO(2)H, CF(3)SO(3)H, and p-TsOH. The palladacycles were observed to coordinate amines and electron rich anilines but not sulfonamides or carboxamides. Analysis of the (t)Bu-NH(2) adduct of the palladacycle 2b (2b·(t)Bu-NH(2)) by NMR spectroscopy (NOE) revealed a cis-coordination of the amine. However, the amine adducts fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…Liu and co-workers also explored the olefination of phenol carbamates with styrenes. [27] Halogenation The Pd-catalyzed ortho-bromination andc hlorination of phenol carbamates with N-bromosuccinimide and N-chlorosuccinimide were reported by Nicholas's group [29] and Rao's group, [30] re-Scheme18. Pd II -catalyzed ortho-arylation of carbamate-protected phenols.…”
Section: Olefinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and co-workers also explored the olefination of phenol carbamates with styrenes. [27] Halogenation The Pd-catalyzed ortho-bromination andc hlorination of phenol carbamates with N-bromosuccinimide and N-chlorosuccinimide were reported by Nicholas's group [29] and Rao's group, [30] re-Scheme18. Pd II -catalyzed ortho-arylation of carbamate-protected phenols.…”
Section: Olefinationmentioning
confidence: 99%
“…The Pd‐catalyzed ortho ‐bromination and chlorination of phenol carbamates with N ‐bromosuccinimide and N ‐chlorosuccinimide were reported by Nicholas's group and Rao's group, respectively (Scheme ). Both methods required the use of p ‐toluenesulfonic acid to activate the N ‐halosuccinimides, consequently enhancing the efficiency of the ortho ‐halogenation reaction.…”
Section: Ortho‐c−h Activation Of Phenolsmentioning
confidence: 99%
“…136 Nicholas demonstrated that protected brominated phenols could be accessed from the corresponding O-arylcarbamates via a Pd-catalyzed oxidative C−H bromination (Scheme 46). 137 Although the authors initially attempted to achieve an ortho-C− H amination reaction, after unsuccessful attempts, they observed that stoichiometric iodination of the corresponding cyclopalladated O-phenyl carbamates could be achieved using NIS. However, when attempting to achieve a catalytic process, they observed a significant background reaction occurred which afforded the undesired para-brominated product.…”
Section: Scheme 32 Pd-catalyzed Ortho-selective C−h Halogenation Of mentioning
confidence: 99%
“…This latter finding was contested in a subsequent publication by Grushin, 179 wherein it was reasoned that the Meisenheimer-type aryl group contained in the ArPd(II)F complex found to undergo carbon−fluorine bond reductive elimination could simply be undergoing a nucleophilic S N Ar reaction with free F − to generate the observed aryl halide. Accordingly, Grushin and co-workers synthesized and characterized analogs of this ArPd(II)F dimer (where Ar = p-NO 2 −C 6 H 4 ), 137 where Ar was a nonMeisenheimer type aromatic and possessed an H, Me, or OMe group (86a−c, Figure 5) from the corresponding ArPd(II)I analogs 85a−c.…”
Section: Carbon−halogen Reductive Elimination From Pd(ii) Complexesmentioning
confidence: 99%
“…We prepared a panel of new palladacycles carrying the various directing groups (Table 1). The pivaloylanilide palladacycle 3 , 20 the phenylurea palladacycle 4 , 21, 22 the phenol ester palladacycle 5 , 23 and the O -phenylcarbamate palladacycle 6 24 were prepared according to the published procedures. On the other hand, the N -phenylcarbamate palladacycles 7 – 20 were prepared by treating the corresponding carbamate with Pd(OAc) 2 and triflic acid in dichloroethane or dioxane at room temperature (see Table S1 in the Supplemental Information for yields).…”
mentioning
confidence: 99%